Analysis of the Relationships Between Crises, Risks and Stock Market Indexes - Fábiánné Játékos, Judit Ilona; Kovács, Tamás (Acta Carolus Robertus, 2023)
Every day, investors and valuation experts are confronted with many problems in determining the value of a company. One of the most difficult areas to plan for is the impact of crises on firm value. After a brief theoretical overview of value creation, risks and crises, this article looks at the general perception of value in the stock market. The main aspect of our analysis is to examine the change in value during crisis periods and to show to what extent this was predictable from stock market expectations.In this context, we have examined the movements of two volatility indexes during the crisis periods of the last 15 years. We find that the VIX index and the S&P 500 index are well matched in each period and can be seen to behave as inverses of each other. The same can be observed in the evolution of the other index analysed, the EURO STOXX 50 and the VSTOXX index. By comparing the US and European indices, we have shown that the indices have been able to perform very differently over the same period, due to different market maturities, different crisis management techniques and the application of a common crisis management concept, or lack thereof.
Keywords: firm value; crisis; risk; volatility index